Operation and Testing of Indirect Field Oriented Control of Asymmetrical Six-Phase Open-Ended Winding Induction Machine Using Hardware-in-Loop (HIL) Emulator - Arif Iqbal; Farhad Ilahi Bakhsh; Girish Kumar Singh (International Transactions on Electrical Energy Systems)
This study deals with an asymmetrical six-phase open-ended winding induction machine in closed loop operation using indirect field-oriented control scheme. The closed loop scheme has been developed by using the two axis (d-q) modeling of six-phase induction machine in rotating synchronous reference frame and can be easily extended to any multiphase machine having the stator winding which are the multiple of three. Operation under steady-state is considered to develop the phasor diagram in closed loop operation of machine in the motoring mode. The performance of the asymmetrical six-phase induction machine (opened ended winding) is investigated in the entire four-quadrant operation. The complete machine drive system was developed by using MATLAB/Simulink, which was used to obtain analytical results in different modes. Furthermore, the analytical results in the motoring mode were experimentally validated through real-time simulation by using Typhoon hardware-in-loop (HIL) emulator.